การประยุกต์การกระตุ้นเชิงกลต่อการเจริญเติบโตและผลผลิตข้าวพันธุ์หอมธรรมศาสตร์ - จิตจักร, วรรณระวี; ชคตระการ, สมชาย; อธินุวัฒน์, ดุสิต; ชุติมานุกูล, พฤกษ์ (Thai Journal of Science and Technology, 2020)
Currently, consumers concern about buying the product from an agro-ecological production system, thus conventional agriculture may be adapted to organic agriculture. Mechanical stimulation was used in organic farming to enhance the growth of economic crops. This study focuses on the effect of touching frequency and duration of mechanical stimulation on the growth and yield of Hom Thammasat rice. The experiment was conducted by using electric duster with a speed of 256.8 cm/min to stimulate rice seeding from day 3 to day 14 after germination with touching durations for 10, 20, and 30 min per time and touching frequency for 1, 2, 3, and 4 times per day. The results revealed that mechanical stimulation with 30 min per time touching durations and 1 time per day or 20 min per time touching durations and 2 times per day significantly (p ≤ 0.05) enhanced leaf width, stem dry weight and root dry weight, meanwhile reducing stem height and root length. Moreover, these two treatments increased Hom Thammasat rice productivity with 1,961 and 2,094 kg per rai, respectively whereas control treatment showed a yield of 938.34 kg per rai.